INTERACTION OF RELIGION AND LOCAL CULTURE IN SYMBOLIC COMMUNICATION OF AGRICULTURAL RUWAT FOR STRENGTHENING INDIGENOUS AUTHORITY ACROSS JAVANESE ETHNICS - Purwanti, Eneng; Anam, Khairil; Ilah Holilah; Kamaluddin Nurdin Marjuni (Penamas, 2025)
This study addresses a critical gap in comparative research on the agricultural rutawt tradition as an integrated model for national food security within Indonesia's ethnic diversity. The objective of this study is to analyze the symbolic communication and value negotiation of Ruwat Pertanian across three communities: Kasepuhan Ciptagelar, located in West Java, Kasepuhan Cicarucub in Banten, and Adirasa in Central Java. A qualitative comparative-ethnographic approach was employed to collect data through in-depth interviews with traditional leaders and direct observations. The results identify three distinct models of cultural resilience: the Conservative Model in Ciptagelar, which strictly preserves ecological authority to maintain food sovereignty; the Integrative Model in Cicarucub, which harmonizes ancestral customs with Islamic values; and the Pragmatic Model in Adirasa, which rationalizes rituals for economic utility. Despite these variations, Ruwat functions as an ecological rite of passage that serves to legitimize spiritual authority and sustainable cultivation norms. These findings offer critical policy implications, suggesting that integrating these diverse local wisdom typologies specifically the leuit system and syncretic practices into national strategies is essential for achieving food sovereignty and religious moderation